2021
DOI: 10.1002/ijc.33691
|View full text |Cite
|
Sign up to set email alerts
|

Causal association of childhood obesity with cancer risk in adulthood: A Mendelian randomization study

Abstract: In observational studies of children and adolescents, higher body weight has been associated with distinct disease outcomes, including cancer, in adulthood. Therefore, we performed a two‐sample Mendelian randomization (MR) study to evaluate the causal effect of childhood obesity on long‐term cancer risk. Single‐nucleotide polymorphisms associated with higher childhood body mass index (BMI) from large‐scale genome‐wide association studies were used as genetic instruments. Summary‐level data for 24 site‐specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
(52 reference statements)
1
12
1
Order By: Relevance
“…In 2016, more than 1.9 billion adults (39%) were overweight (body mass index (BMI) ≥ 25) with over 650 million (13%) of those being obese (BMI ≥ 30) [1]. Alarmingly, more than 340 million children and adolescents (ages [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] were overweight or obese in 2016 and 39 million children younger than 5 years of age were overweight or obese in 2020 [1]. In the United States of America, the latest data brief from the National Center for Health Statistics reports a prevalence of obesity in adults aged 20 years or older of 42.4% in 2017-2018, which is a considerable increase from 33.7% in 2007-2008 [2].…”
Section: Epidemiology Of Obesity and Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, more than 1.9 billion adults (39%) were overweight (body mass index (BMI) ≥ 25) with over 650 million (13%) of those being obese (BMI ≥ 30) [1]. Alarmingly, more than 340 million children and adolescents (ages [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] were overweight or obese in 2016 and 39 million children younger than 5 years of age were overweight or obese in 2020 [1]. In the United States of America, the latest data brief from the National Center for Health Statistics reports a prevalence of obesity in adults aged 20 years or older of 42.4% in 2017-2018, which is a considerable increase from 33.7% in 2007-2008 [2].…”
Section: Epidemiology Of Obesity and Pancreatic Cancermentioning
confidence: 99%
“…Importantly, the association between obesity and risk of PDAC was stronger in men than in women [16]. Besides the importance of early adulthood, growing evidence suggests that adolescent and childhood obesity is also linked to an increased risk of developing PDAC later in life [17][18][19][20]. Here, it is imperative to distinguish the effect of obesity during early cancer development (risk factor for early tumor promotion) from its sometimes-paradoxical effects in the late-stage, advanced disease, where obesity occasionally appears to be associated with improved outcome (obesity paradox) [21][22][23].…”
Section: Epidemiology Of Obesity and Pancreatic Cancermentioning
confidence: 99%
“…A Swedish study of more than 200,000 men who had their height and weight measured in adolescence, reported a more than twofold higher risk for later life colorectal cancer for the obese group (BMI ≥30 kg/m 2 ) when compared with the normal weight group (BMI 18.5-<25 kg/m 2 ) (33). A large Israeli study of almost 1.8 million men and women showed that being overweight and obese at adolescence was associated with higher colon cancer risk for both men (HR for overweight, A recent MR study examined the associations between childhood obesity and cancer risk without taking into account adult body size, using a genetic instrument of 15 SNPs from a GWAS of 47,541 children from the Early Growth Genetics (EGG) consortium (35). Effect estimates from this study did not support a positive relationship between childhood BMI and overall colorectal cancer (OR, 1.11; 95% CI, 0.93-1.32) (35).…”
Section: Discussionmentioning
confidence: 99%
“…A large Israeli study of almost 1.8 million men and women showed that being overweight and obese at adolescence was associated with higher colon cancer risk for both men (HR for overweight, A recent MR study examined the associations between childhood obesity and cancer risk without taking into account adult body size, using a genetic instrument of 15 SNPs from a GWAS of 47,541 children from the Early Growth Genetics (EGG) consortium (35). Effect estimates from this study did not support a positive relationship between childhood BMI and overall colorectal cancer (OR, 1.11; 95% CI, 0.93-1.32) (35). Results from our analyses, that crucially adjusted for adult body size, also reflect little evidence of a positive relationship between early life body size and later life colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation